The review of serbian тranslation of the handbook on Social stratification in BRIC countries - Changes and Perspectives - Vratuša, Vera (Sociološki pregled, 2018)
Serbian State Publisher of Thextbooks from Belgrade once more confrmed its dedication to the mission of contributing to increase the quality of education and development of science and culture in Serbia through publishing important contemporary educational texts of high quality.Just one year afer the World Scientifc Publishing Co. in Singapore published the English original (2013), they oﬀered to the domestic social science community and general public the Serbian translation of the results of the pioneering comparative research of Social stratifcation in BRIC countries - Changes and Perspectives, which was published in 2014 by Serbian State Publisher of Thextbooks. Tis path breaking compendium edited leading sociologists with up to date research fndings from China (Li Peilin, Institute for sociology of the Chinese academy of social sciences, CASS, 2005), Russia (M.K. Gorshkov, Institute for sociology of the Russian academy of sciences, RAS, 2009), Brazil (Celi Scalon, Federal University in Rio de Janeiro, 2009) and India (K.L. Sharma, National university in Jaepur, 2010). Mentioned editors gathered teams of researchers in respective countries. Only K.L. Sharma, wrote alone nine thematic chapters on: social stratifcation changes; working class; peasants; entrepreneurs; middle class; income inequality; educational inequality; consumption and class consciousness and values, paying special attention to castes specifc to Indian society.